Family members at the epicentre of policy discourses: Agency, negotiation, and local practices - Nandi, Anik; Zabrodskaja, Anastassia (Sociolinguistic Studies, 2024)
The articles in this thematic issue of Sociolinguistic Studies, ‘Family as a language policy regime: Agency, negotiation and local practices’, are concerned with the impact of family (language policy) among the minority population, whether indigenous or otherwise, on the sociolinguistic makeup of the contemporary policy regimes worldwide. Although family language policy is already a well-established domain of inquiry, this issue points to the wide range of cases from around the world, including Cyprus, Estonia, Germany, Iran, Lithuania, Northern Ireland, Spain, Sweden, the United Kingdom, and Zimbabwe, to understand how (individual) pathways are formed and choices made in favour of language and cultural maintenance. While covering a wide range of factors and perspectives that contribute to our understanding of families’ linguistic behaviour and the broader social implications of the discipline, these papers emphasise the complex relationships between language, culture, politics, and socioeconomic factors in today’s global multilingual and multicultural mosaic. This edition further underlines a number of present-day requirements in the field, such as being able to examine children’s or extended family members’ agency, use of digital technologies for language maintenance, different forms of parental language planning and activism to mention a few. The collection has emerged in the wake of a symposium ‘Family as a language policy regime: Agency, practices and negotiation’ at the 20th AILA World Congress (19–20 July, 2023, Lyon, France) and a closed call for papers.